MONITORING OF THE PERFORMANCE EFFICIENCY OF THE EQUIPMENT AT THE ENTERPRISES OF AVIATION INSTRUMENTATION - Petr P. Dobrov (Модернизация, инновация, развитие, 2016)
The article elaborates the proposals to improve the systems for monitoring performance of the equipment at the enterprises of aviation instrument. The relevance of the study due to the fact that the aviation instrument-making industry of the Russian Federation can play a role as a key factor in enhancing the competitiveness of the national economy. Currently, the global aviation market is fairly saturated, it competition is not between individual companies and between the aviation powers. The role of an efficient industrial production is largely dependent on the amount, structure, technical condition and the level of utilization of fixed assets. Specificity of high-tech high-tech production presupposes the existence of a specific fleet of expensive and unique equipment; a high degree of novelty products, single or small-scale type of production that determines the high cost of production of a unit of production; high demands on the staff . The paper noted that the production capacity is an essential tool for production planning process, which allows to determine the optimal work shifts Park main technological equipment and production program to justify the enterprises of sphere of aviation instrument. On the basis of the modification of OEE method, a stochastic model is proposed, which allows to display the efficiency of the productive capacity of the high-tech enterprises of sphere of aviation instrument in the form of multi-dimensional size and much more accurately identify the relationship between its elements.